2019
DOI: 10.1590/1678-5150-pvb-6141
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description of ovary and uterus of the nurse shark (Ginglymostoma cirratum) caught off at the Fortaleza coast, Northeast Brazil

Abstract: The nurse shark, Ginglymostoma cirratum (Bonnaterre, 1778) is one of the most studied species of elasmobranchs. However, the knowledge of their reproductive biology is still relatively rare, particularly in the western South Atlantic. This study aimed to describe the morphology of the uterus and the ovary of G. cirratum, based on specimens caught off at the Fortaleza/CE coast, northeast Brazil. Samples were collected from September 2012 to June 2013, from regular landings of artisanal fishing, which commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…), together indicating that female maturity might occur at a smaller size in the TCI. Similarly, dissections of ten females from Brazilian waters revealed that the process of maturation may commence at only 152 cm TL (Rêgo et al 2019), suggesting that full maturity might also be attained at a smaller size there than has been reported from Florida (Castro 2000). In the case of males, Pikitch et al (2005) reported that male maturity occurred between 185 and 200 cm TL at Glover's Reef atoll (Belize), based on clasper condition.…”
Section: Discussionmentioning
confidence: 84%
“…), together indicating that female maturity might occur at a smaller size in the TCI. Similarly, dissections of ten females from Brazilian waters revealed that the process of maturation may commence at only 152 cm TL (Rêgo et al 2019), suggesting that full maturity might also be attained at a smaller size there than has been reported from Florida (Castro 2000). In the case of males, Pikitch et al (2005) reported that male maturity occurred between 185 and 200 cm TL at Glover's Reef atoll (Belize), based on clasper condition.…”
Section: Discussionmentioning
confidence: 84%